Taqyim Ta'lim Al-Qira’ah Al-Jahriyah bi Kitab Mubtadi fi Silsilah Al-Lisan ala Asas Tahlil Ihtiyajat Al-Manhaj Al-Mustaqil - Husna, Muhammad Ahsanul; Inayah, Inayah (Institut Agama Islam Negeri (IAIN) Metro, 2023)
This research aims to characterize the teaching of read-aloud with kitāb-mubtadi' in Silsilah-Lisān. Evaluating on it based on Kurikulum Merdeka's need analysis. This study is experiment evaluation, data collected from test and observation. Data analysis by Miles and Huberman model, with collecting, displaying, reducing and conclusions. Sample is 177 students of UIN Walisongo. The result is Pre-test started with equivalent value 58.59. The research passed on 16 subject-materials and ended with the post-test and equivalent value is 60,65. The result of the differences in the value of the average was 2.06 in the grade of C. So, the use of kitāb-mubtadi' was not effective on it. The evaluation is a) Project-based learning evaluation, b) Using read-aloud in public speaking training, c) Suiting the study plan with the theory of read-aloud, including the competencies of vocal performance, intonation, and diction, d) applied in local culture topics.